O que faz uma casa? Notas sobre a arte de habitar. - João Carlos de Almeida Gaspar (2013)
The question ''what makes a home?''/''what a home makes?'', title of this dissertation, further than inquire us about the components of all kinds that get together to make home happen, lead us to the recognition of 'home' as a subjectivity producer. This master's dissertation leans over the dynamic relationship between the person and the inhabitation space. The conscience that this relationship between the person and the home's space exceeds the sphere of objectivity, lead us to the recognition of 'home' as the center of the person's territorial realization. Assuming 'home' as an expressive realization - more than a material work or a set of uses - we propose a research on the roll of architecture in the construction of home. Architecture, working over the material sphere, is not indifferent to the production of subjectivity that will be part of when inhabited. Recognizing the inhabitant´s territory, the architect must find the expansion fields of his work, in the way of get closer to the inhabitant's needs and wishes. The approximation to the subjective dimension witch home is simultaneously product and producer is made through the cartography of the inhabited space. This intention of taking the problem of home's production from the point of the living space, take us to the adoption of the self experience as the object of study. The visit to the inhabited homes pretends to find in its various dimensions - spacial structure, forms of occupation, routines, habits, environments and maturation process - forms of availability of the material construction to the inhabitant territorial realization. Such forms, in their turn, will be evaluated as architectural models, as elements to be par of the architectural lexis with which the constructed space is though and produced. The theory framework of this home's inquiry is made from the convocation of architectural practice and investigation themes but also of other disciplinary areas that embrace the study of the living space. The heterogeneousness of the study's contents lead to the production of various sets of records, with which this work is set up.